Long Chain Fatty Acids as Modulators of Immune Cells Function: Contribution of FFA1 and FFA4 Receptors - Hidalgo, Maria A.; Carretta, Maria D.; Burgos, Rafael A. (Frontiers in Physiology, 2021)
Long-chain fatty acids (LCFA) are molecules that act as metabolic intermediates and constituents of membranes; however, novel roles as signaling molecules in immune function have also been demonstrated. The presence of free fatty acid (FFA) receptors on immune cells has contributed to the understanding of this new role of LCFAs in immune function, showing their role as anti-inflammatory or pro-inflammatory molecules and elucidating their intracellular mechanisms. FFA1 and FFA4 receptors, also known as GPR40 and GPR120, respectively, have been described in macrophages and neutrophils, two key cells mediating the innate immune response. The ligands of FFA1 and FFA4 receptors induce the release of a myriad of cytokines through well-defined intracellular signaling pathways. In this review, we discuss the cellular responses and intracellular mechanisms activated by LCFA, such as oleic acid, linoleic acid, palmitic acid, docosahexaenoic acid (DHA), and eicosapentaenoic acids (EPA), in T-cells, macrophages, and neutrophils, as well as the role of FFA1 and FFA4 receptors in immune cells.